SIMULATION OF CLIMATE CHANGE IMPACT ON WHEAT PRODUCTION IN THE TIARET REGION OF ALGERIA USING THE DSSAT MODEL - Waffa, Rezzoug; Benoit, Gabrielle (European Scientific Journal, ESJ, 2015)
It is now commonly accepted that climate changes is expected to have important effects on diverse economic sectors. Agricultural sector is particularly exposed to changes with climate variability and change due to its influence on production. Predicting the potential effects of climate change on crop yields requires a model witch simulate the crop respond to weather variation. Crop models have been used extensively to predict yield response to various SRES (Special Report Emission Scenarios) scenarios of climate change. The main objective of this study is the use of DSSAT model to simulate and to estimate wheat yield prediction under two climate change scenarios (A2 and B1) in the Tiaret region for adaptation measures and mitigation. The simulation results obtained from this study revealed that the use of the model DSSAT provides an efficient method for evaluating impact of changing climate on wheat production. Adaptation measures to mitigate the potential impact of climate change included possible changes in sowing dates and genotype selection.